2001
DOI: 10.1183/09031936.01.99055301
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in patients with idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) was reported to be associated with increased risk of lung cancer as a result of the occurrence of atypical or dysplastic epithelial changes in fibrosis which progressed to invasive malignancy. In that situation, the cancer will develop in the area of major fibrosis. To investigate the direct relationship between fibrosis and cancer development, the real concordance rate of the two lesions in the chest computed tomography (CT) was analysed and compared to the histological typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
170
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(187 citation statements)
references
References 18 publications
15
170
1
1
Order By: Relevance
“…In particular, the incidence of lung cancer in patients with idiopathic pulmonary fibrosis (IPF) is higher than in the general population, with relative risks reported to be from 7 to 14 (1)(2)(3)(4)(5). Kawasaki et al (6) reported that IPF was found in 7.5% of surgically-resected lung cancer cases.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the incidence of lung cancer in patients with idiopathic pulmonary fibrosis (IPF) is higher than in the general population, with relative risks reported to be from 7 to 14 (1)(2)(3)(4)(5). Kawasaki et al (6) reported that IPF was found in 7.5% of surgically-resected lung cancer cases.…”
Section: Introductionmentioning
confidence: 99%
“…6 An increased incidence of carcinomas, such as squamous cell carcinoma and adenocarcinoma, mainly located in peripheral lung areas, has been reported in IPF patients. [7][8][9] Whether the appearance of abnormal epithelial cells protects or promotes fibrosis remains uncertain. 10 Several experimental and human studies reported a pro-fibrogenetic influence of metaplastic epithelial cells through the secretion of factors favoring fibrotic processes.…”
mentioning
confidence: 99%
“…However, the size of this study and the magnitude of increased incidence strongly suggest a positive association. Subsequent research has further defined the association with increased risk reported in male IPF patients who smoke with a similar frequency of histological cancer subtypes observed in non-IPF sufferers (Park et al, 2001) supporting historical observations (Stack et al, 1972). However, other studies have failed to confirm an association between IPF and malignancy although varying methodology, each with inherent risk of errors, means that a degree of uncertainty remains (Samet, 2000).…”
Section: Ipf As a Risk Factor For Lung Cancermentioning
confidence: 95%